Biostimulatory Action of Vegetal Protein Hydrolysate Compensates for Reduced Strength Nutrient Supply in a Floating Raft System by Enhancing Performance and Qualitative Features of “Genovese” Basil - Ciriello, Michele; Formisano, Luigi; Kyriacou, Marios C.; Colla, Giuseppe; Graziani, Giulia; Ritieni, Alberto; De Pascale, Stefania; Rouphael, Youssef (Frontiers in Plant Science, 2022)
The floating raft constitutes a valuable system for growing herbs as it effectuates high yield and prime functional quality. However, the pressing need for advancing sustainability in food production dictates the reduction of chemical fertilizer inputs in such intensive production schemes through innovative cultivation practices. In this perspective, our work appraised the productive and qualitative responses of two ‘Genovese’ basil genotypes (Eleonora and Italiano Classico) grown in a floating raft system with nutrient solutions of varied electrical conductivity (EC; 2 and 1 dS m–1) combined with root application of protein hydrolysate biostimulant at two dosages (0.15 and 0.3 0 ml L–1 of Trainer®). The phenolic composition, aromatic profile and antioxidant activities (ABTS, DPPH, and FRAP) of basil were determined by UHPLC/HRMS, GC/MS, and spectrophotometry, respectively. ‘Eleonora’ demonstrated higher number of leaves (37.04 leaves per plant), higher fresh yield (6576.81 g m–2) but lower polyphenol concentration (1440.81 µg g–1 dry weight) compared to ‘Italiano Classico’. The lower EC solution (1 dS m–1) increased total phenols (+32.5%), ABTS, DPPH, and FRAP antioxidant activities by 33.2, 17.1 and 15.8%, respectively, and decreased linalool relative abundance by 5.5%. Biostimulant application improved crop performance and increased total phenolic concentration in both genotypes, with the highest phenolic concentration (1767.96 µg g–1 dry weight) registered at the lowest dose. Significant response in terms of aromatic profile was detected only in ‘Eleonora’. Our results demonstrate that the application of protein hydrolysate may compensate for reduced strength nutrient solution by enhancing yield and functional quality attributes of ‘Genovese’ basil for pesto.